[Original papers and letters relating to West Africa, 1886] - Church Missionary Society; University of Birmingham Library; Adam Matthew Digital (Adam Matthew Digital, 1886)
A collection of ms. letters and reports from West Africa, in various hands, reporting on missionary work. There is a detailed typescript precis (29 leaves) at start of collection